Diplomasi Pertahanan Siber Indonesia: Strategi, Tantangan dan Prospek - Bintang Hafizh Setiawan; Hesti Rosdiana; Reja Reja (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The development of information and communication technology (ICT), particularly the use of Artificial Intelligence (AI), the Internet of Things (IoT), and big data, has transformed Indonesia's national security threat landscape. Threats that previously focused on traditional military aspects have now shifted to non-traditional cyber threats, such as cyberattacks, digital espionage, and infrastructure sabotage. According to PROXSIS IT GRC data, in 2024, more than 19 million cyberattacks were recorded against websites in Indonesia. While this figure is a decrease compared to the previous year, this trend is thought to reflect a shift towards more structured and organized tactics by threat actors. In response, the Indonesian government established the National Cybersecurity Action Plan 2024–2028 as a strategic guideline. Furthermore, cyber diplomacy is being promoted through bilateral and multilateral cooperation, for example through the signing of memorandums of understanding (MoUs) with the UK and Kaspersky. This cooperation includes the exchange of intelligence information, strengthening human resource capacity, raising public awareness regarding cybersecurity, and protecting critical information infrastructure. This study uses non-traditional security theory and defense diplomacy to analyze the strategies, challenges, and prospects of Indonesia's cyber policy. The analysis demonstrates that cyber defense diplomacy plays a crucial role as an instrument for integrating technology, regulation, and international collaboration in safeguarding digital sovereignty. In addition to strengthening threat detection and mitigation capabilities, this diplomacy also builds networks of trust with partner nations, which is essential amidst the increasing complexity of global threats. Therefore, in the era of digital globalization, full of interconnections, cyber defense diplomacy serves not only as a national protection tool but also as Indonesia's contribution to global cybersecurity stability. This effort prioritizes synergy between technological innovation, law enforcement, and sustainable international cooperation.